Determinants of financial stress and recovery during the great recession - Joshua Aizenman; Gurnain Kaur Pasricha (University of California, Economics Department, 2010)
In this paper, we explore the link between stress in the domestic financial sector and the capital flight faced by countries in the 2008-9 global crisis. Both the timing of emergence of internal financial stress in developing economies, and the size of the peak-trough declines in the stock price indices was comparable to that in high income countries. The main difference was the greater dispersion of the decline in low and middle countries, with standard deviation that was twice that of the high income countries. Deleveraging of OECD positions seemed to dominate the patterns of capital flows during the crisis. While high income countries on average saw net capital inflows and net portfolio inflows during the crisis quarters, compared to net outflows for developing economies, the indicators of banking sector stress were higher for high income economies on average than for developing economies. De-facto openness was associated with greater capital outflows and greater portfolio outflows. Larger total external debt minus reserves, external portfolio assets/GDP and external portfolio liabilities/GDP were also associated with greater internal financial stress. Countries with better banking supervision and higher bank capital to assets ratio saw smaller declines in banking sector stock prices. Countries with more concentrated banking sectors also had more stable banking sectors in this crisis. Intriguingly, the same was true for more competitive but better supervised banking sectors. Central banks also seem to have responded more in countries with greater de-facto openness.
Keywords: F32; G15; 330; great recession; determinants of financial crisis; capital flows; decoupling; Finanzmarkt; Börsenkurs; Volatilität; Kapitalmobilität; Kapitalflucht; Auslandsverschuldung; Finanzmarktkrise; Welt